How Do Museums Fit into our Notions of Adult Education? - Robin S. Grenier (Adult Education Research Conference, 2007)
In order to offer successful learning opportunities for adults throughout their lives it is important to explore the role of museums in adult education and learning. The goal of this roundtable is to address the long held notion that museums are valid places of adult learning and call attention to its diminished presence in adult education research and discourse.